Fracture patient experience in undergoing traditional massage therapy (Topu Bara) in Maluku Province: phenomenology study - Wabula, La Rakhmat; Umamity, Syahfitrah; Fitriasari, Endah; Lombonaung, Ellen; Windari, Arindiah Puspa; Tehupelasury, Fahrunnissa (Jurnal Ners, 2022)
Introduction: In Indonesia, especially among the Maluku people, there was a culture of seeking traditional fracture treatment, namely "Topu Bara." Their belief has been passed down from generation to generation who believe that conventional medicine (Topu Bara) can cure the problem of fractures experienced by sufferers  The study aimed to explore patient's fracture healing experience in Topu Bara Methods: The method used wasa  phenomenological study that used deep interviews from August to September 2021  The participants were taken by purposive sampling, adults aged 21 to 59-years old, and were in the second or more of healing series  Data originated from 15 participants  Interviews were recorded, transcribed verbatim, and subjected to Collaizi analysis. Results: The results of the study found 7 themes, including causes of fracture, time events, action taken directly after inside, pain experiences during handling in "Topu Bara" therapy, coping of the patients, pain management, and advice given by healer to other participants. Conclusions: Most of them stated that safety and comfort were the priority for fracture healing  The concept of culture in the behavioral alteration of fracture healing can have an impact on the participants.